Direct control of electron spin at an intrinsically chiral surface for highly efficient oxygen reduction reaction - Xia Wang; Mayra Peralta; Xiaodong Li; Paul V. Möllers; Dong Zhou; Patrick Merz; Ulrich Burkhardt; Horst Borrmann; Iñigo Robredo; Chandra Shekhar; Helmut Zacharias; Xinliang Feng; et al. (Proceedings of the National Academy of Sciences, 2025)
The oxygen reduction reaction (ORR) in acidic media suffers from sluggish kinetics, primarily due to the spin-dependent electron transfer involved. The direct generation of spin-polarized electrons at catalytic surfaces remains elusive, and the underlying mechanisms are still controversial due to the lack of intrinsically chiral catalysts. To address this challenge, we investigate topological homochiral PdGa (TH PdGa) crystals with intrinsically chiral catalytic surfaces for ORR. Through spin-resolved photoemission spectroscopy and theoretical simulations, we show that both structural chirality and spin–orbit coupling are critical for inducing spin polarization at the surface of TH PdGa. As a result, TH PdGa achieves a kinetic current density over 100 times higher than the achiral PdGa (AC PdGa) at 0.85 V versus the reversible hydrogen electrode. This work underscores the pivotal role of spin polarization in enhancing acidic ORR activity and lays the groundwork for the rational design of chiral catalysts for spin-dependent catalysis.